Mekanisme Simpanan Haji dan Umrah (SHAUM) di KSPPS Khidmatul Ummah Bogor - Salwa Aini Febrianti; Dedi Junaedi; Erna indiastuti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2021)
This study aims to analyze the financing mechanism of Hajj and Umrah in KPPPS Khidmatul Ummah Bogor. The method used is descriptive qualitative analysis based on field studies and observations during PPL. The results are as follows: the mechanism of umrah and hajj savings products in KSPPS Khidmatul Ummah consists of several procedures such as: opening savings accounts, receiving savings deposits, withdrawing savings and closing accounts. The contract used has been in accordance with the principles of sharia, namely using the revenue sharing system and mudharabah contract. In fatwa DSN No.07/DSN-MUI/IV/2000 on mudharabah and the foundation of sharia law In accordance with the Qur'an and hadith that have been explained in Surat An-nisa 'verse 29 and hadith from Ibn Majjah.